Apolipoprotein A-I gene transfer exerts immunomodulatory effects and reduces vascular inflammation and fibrosis in ob/ob mice - Spillmann, Frank (J Inflamm (Lond), 2016)
BACKGROUND: Obesity is associated with vascular inflammation, fibrosis and reduced high-density lipoproteins (HDL)-cholesterol. We aimed to investigate whether adenoviral gene transfer with human apolipoprotein (apo) A-I (Ad.A-I), the main apo of HDL, could exert immunomodulatory effects and counteract vascular inflammation and fibrosis in ob/ob mice. METHODS: Ad.A-I transfer was performed in 8 weeks (w) old ob/ob mice, which were sacrificed 7 w later. The aorta was excised for mRNA analysis and the spleen for splenocyte isolation for subsequent flow cytometry and co-culture with murine fibroblasts. HDL was added to mononuclear cells (MNC) and fibroblasts to assess their impact on adhesion capacity and collagen deposition, respectively. RESULTS: Ad.A-I led to a 1.8-fold (p < 0.05) increase in HDL-cholesterol versus control ob/ob mice at the day of sacrifice, which was paralleled by a decrease in aortic TNF-α and VCAM-1 mRNA expression. Pre-culture of MNC with HDL decreased their adhesion to TNF-α-activated HAEC. Ad.A-I exerted immunomodulatory effects as evidenced by a downregulation of aortic NOD2 and NLRP3 mRNA expression and by a 12 %, 6.9 %, and 15 % decrease of the induced proliferation/activity of total splenic MNC, CD4+, and CD8+ cells in ob/ob Ad.A-I versus control ob/ob mice, respectively (p < 0.05). Ad.A-I further reduced aortic collagen I and III mRNA expression by 62 % and 66 %, respectively (p < 0.0005), and abrogated the potential of ob/ob splenocytes to induce the collagen content in murine fibroblasts upon co-culture. Finally, HDL decreased the TGF-ß1-induced collagen deposition of murine fibroblasts in vitro. CONCLUSIONS: Apo A-I transfer counteracts vascular inflammation and fibrosis in ob/ob mice. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12950-016-0131-6) contains supplementary material, which is available to authorized users.